EFEKTIVITAS PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENGENTASAN KEMISKINAN (STUDI KASUS DI DESA SEI BELUTU KECAMATAN SEI BAMBAN KABUPATEN SERDANG BEDAGAI) - Rajagukguk, Melani Tionida; Panjaitan, Maringan; Rajagukguk, Jonson (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to evaluate the effectiveness of PKH implementation in poverty alleviation efforts in Sei Belutu Village, Sei Bamban District, Serdang Bedagai Regency. This study uses a qualitative descriptive approach with data collection methods through interviews, observations, and documentation of beneficiaries, PKH facilitators, and other related parties. The results of the study indicate that PKH has a positive impact in increasing access to education for children from poor families and encouraging the use of health facilities, especially for pregnant women and toddlers. In addition, PKH also helps ease the economic burden of beneficiary families. However, the effectiveness of the implementation of this program still faces a number of obstacles, such as delays in disbursement of funds, lack of public understanding of the obligations that must be fulfilled as recipients of assistance, and inaccuracy in targeting recipients. Lack of supervision and assistance are also factors that influence the success of this program in achieving its main objectives. Based on the research findings, improvements are needed in the PKH implementation mechanism, including increasing socialization to beneficiaries, accelerating the disbursement process, and strengthening the monitoring and evaluation system so that this program can run more optimally and effectively in alleviating poverty in Sei Belutu Village